Correction: In situ spectroscopic investigations of MoOx/Fe2O3 catalysts for the selective oxidation of methanol. Issue 11 (18th May 2018) - Brookes, Catherine; Bowker, Michael; Gibson, Emma K.; Gianolio, Diego; Mohammed, Khaled M. H.; Parry, Stephen; Rogers, Scott M.; Silverwood, Ian P.; Wells, Peter P.
Abstract : Correction for ' In situ spectroscopic investigations of MoO x /Fe2 O3 catalysts for the selective oxidation of methanol' by Catherine Brookes et al., Catal. Sci. Technol., 2016, 6, 722–730.